THE CAUSES, PREVALENCE AND THE RAVAGING COROLLARIES OF ILLEGAL CROSS BORDER TRADES (ICBTs) ON NIGERIA’S ECONOMY - Sunday, Ameh Ojonugwa (Advances in Social Sciences Research Journal, 2020)
This study elucidate the causes, prevalence and ravaging corollaries of Illegal Cross Border Trades ( ICBTs ) on the Nigerian economy with a view to proffering workable solutions. The study is anchored on the broken window theory. A sample size of 75 respondents was arrived at using Taro Yamane’s formula and to ensure greater representation of the sample relative to the population, proportionate stratified random sampling technique was used for the selection of respondents. Quantitative data were obtained from the 75 selected respondents who were Nigeria Customs Service staff and who resides in Illela and Sabon-Birni border areas. These areas are in Sokoto State of Nigeria but share boundary with Niger Republic. Data collected were analyzed in line with study objectives and research hypotheses, using descriptive and inferential statistics at 0.05 level of significance. Findings revealed that though policies and programmes tailored along the line of curbing and ameliorating smuggling are made yearly, the rate of ICBTs continue to increase. Reasons for this include preference for foreign goods, craze for cheaper prices of goods, connivance between smugglers and some security personnel, paucity of border security. It was also found that the rate of ICBTs in the studied areas and by projection the nation is on the high side, thus contributing enormously to the receding economy. The study recommended among other things that a threesome relationship between Nigeria Customs Service, traditional elites and local settlers should be developed or built into government policies for curbing ICBTs; there should be a continuous orientation and re-orientation of the people by government agencies and other stakeholders; government increase employment opportunities and reduction in poverty rate; and government should be apt in carrying out statutory responsibilities. Keywords: Border, Illegal Cross Border Trade, Security personnel, Smugglers, Threesome relationship.